2016
DOI: 10.15283/ijsc16021
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Thymoquinone, α7 Receptor Agonist and α7 Receptor Allosteric Modulator on the Cerebral Cortex in Experimentally Induced Alzheimer's Disease in Relation to MSCs Activation

Abstract: Background and ObjectivesAlzheimer’s disease (AD) is the most common form of dementia among older persons. Thymoquinone (TQ) has anti-inflammatory, anticonvulsant and antioxidant activity. A novel α7 nicotinic acetyl choline receptor (α7 nAChR ) agonist (PNU- 282987) have been identified to enhance the cognitive performance. An alternative treatment strategy via compounds known as nicotinic “positive allosteric modulators” (PAMs) has been reported. This study was designed to investigate the combination of PAM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 27 publications
0
4
0
3
Order By: Relevance
“…Recently, in an animal model of AD [lipopolysaccharide(LPS)-induced neuroinflammation in rats] it was tested the combination of PNU-120596, a positive allosteric modulator (PAM) of α7 nicotine acetyl choline receptor (nAChR), with the specific nAChR agonist PNU-282987 or with TQ (Ibrahim AbdEl Fattah et al, 2016 ). Data reported that TQ or the α7 nAChR agonist in combination with the PAM had a pivotal role in the treatment of AD, by reducing the neuroinflammation, and by activating the mesenchymal stem cells (MSCs).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, in an animal model of AD [lipopolysaccharide(LPS)-induced neuroinflammation in rats] it was tested the combination of PNU-120596, a positive allosteric modulator (PAM) of α7 nicotine acetyl choline receptor (nAChR), with the specific nAChR agonist PNU-282987 or with TQ (Ibrahim AbdEl Fattah et al, 2016 ). Data reported that TQ or the α7 nAChR agonist in combination with the PAM had a pivotal role in the treatment of AD, by reducing the neuroinflammation, and by activating the mesenchymal stem cells (MSCs).…”
Section: Resultsmentioning
confidence: 99%
“…The PAM of α7 nAChRs is known as PNU-120596. 97 Recently, studies aimed at investigating the combination of PAM of α7 nAChRs with PNU-282987 (α7 nAChR agonist) or with TQ as a possible treatment for AD in an animal model using histological, histochemical, immunohistochemical, and morphometric methods.…”
Section: Neuroprotective Effectsmentioning
confidence: 99%
“…LPS causes acidophilic masses, deformed neurons, Congo red (+ve) masses, and reduced cAMP response element-binding protein (CREB) phosphorylation (phospho-CREB) immunoexpression. Concerning histological, histochemical, and immunohistochemical studies, TQ or α 7 nicotinic acetylcholine receptor agonist combined with PAM can have an important role in treatment of AD [ 91 ]. In a recent study, TQ improves LPS-induced learning and memory impairments in rats by attenuating hippocampal cytokine levels and brain tissue oxidative damage [ 84 ].…”
Section: Neuropharmacological Potential Of Thymoquinonementioning
confidence: 99%